Rhabdoviral Endogenous Sequences Identified in the Leishmaniasis Vector Lutzomyia longipalpis Are Widespread in Sandflies from South America - Tempone, Antonio J; Zezza-Ramalho, Monique de Souza; Borely, Daniel; Pitaluga, André N; Brazil, Reginaldo Peçanha; Brandão-Filho, Sinval P; Pessoa, Felipe A C; Bruno, Rafaela V; Carvalho-Costa, Filipe A; Salomón, Oscar D; Volf, Petr; Burleigh, Barbara A; et al. (Viruses, 2024)
Sandflies are known vectors of leishmaniasis. In the Old World, sandflies are also vectors of viruses while little is known about the capacity of New World insects to transmit viruses to humans. Here, we relate the identification of RNA sequences with homology to rhabdovirus nucleocapsids (NcPs) genes, initially in the Lutzomyia longipalpis LL5 cell lineage, named NcP1.1 and NcP2. The Rhabdoviridae family never retrotranscribes its RNA genome to DNA. The sequences here described were identified in cDNA and DNA from LL-5 cells and in adult insects indicating that they are transcribed endogenous viral elements (EVEs). The presence of NcP1.1 and NcP2 in the L. longipalpis genome was confirmed in silico. In addition to showing the genomic location of NcP1.1 and NcP2, we identified another rhabdoviral insertion named NcP1.2. Analysis of small RNA molecules derived from these sequences showed that NcP1.1 and NcP1.2 present a profile consistent with elements targeted by primary piRNAs, while NcP2 was restricted to the degradation profile. The presence of NcP1.1 and NcP2 was investigated in sandfly populations from South America and the Old World. These EVEs are shared by different sandfly populations in South America while none of the Old World species studied presented the insertions.
Keywords: Lutzomyia longipalpis; endogenous viral element; Brazílie; Rhabdoviridae; Psychodidae; DNA; Leishmaniasis; PIWI-RNA; leishmanióza; Animals; lidé; Brazil; RNA; Jižní Amerika; Humans; zvířata; South America